The impact of the COVID-19 pandemic on the personal finance: A comparative analysis of Poles and Slovaks - Krzysztof Waliszewski (Financial Internet Quarterly, 2022)
The COVID-19 pandemic, due to its prevalence, has affected all spheres of socio-economic life, in particular household finances. The aim of the article is to present the impact of the pandemic on the financial situation of Poles and Slovaks who use robo-advisory services, including their financial behaviour and investments. The methodology of the article involves literature analysis, statistical data and the author's own empirical survey. The empirical study aims to verify the research hypothesis: the COVID-19 pandemic influenced the personal finances of Poles and Slovaks who use robo-advice, although this impact was not the same in all areas of personal finance, nor in relation to investment plans after the pandemic. During the pandemic, most of the respondents had lower expenses, but in the future more than half of the respondents did not plan to change the amount of their expenses. Most of the surveyed people increased their savings during the pandemic. Poles more often admitted that they invested more during the pandemic, while more Slovaks than Poles invested the same amount during the pandemic. On the other hand, the Slovak respondents declared that after the pandemic they intend to invest greater sums than Poles indicated.
Keywords: D14; G11; G51; 330; personal finance; COVID-19 pandemic; personal budget; investments; savings